Correlation Analysis of Staphylococcus aureus Drug Resistance and Virulence Factors with Blood Cell Counts and Coagulation Indexes - Jing Wei; Kaihui Ma; Yuan Zhang; Xincheng Yang; Qiao Tang; Zhenlin Nie (International Journal of Clinical Practice)
Objective. The influence of different Staphylococcus aureus variants on blood cells and coagulation system was evaluated by investigating the carrying status of drug resistance genes and virulence genes of methicillin-resistantStaphylococcus aureus (MRSA) and methicillin-sensitiveStaphylococcus aureus (MSSA). Methods. A total of 105 blood culture-derivedStaphylococcus aureus strains were collected. The carrying status of drug resistance genes mecA and three virulence genes tst, pvl, and sasX was analyzed by polymerase chain reaction (PCR). The changes in routine blood routine counts and coagulation indexes of patients infected with different strains were analyzed. Results. The results showed that the positive rate of mecA was consistent with that of MRSA. Virulence genes tst and sasX were detected only in MRSA. Compared with MSSA, patients infected with MRSA or MSSA patients infected with virulence factor, leukocyte count and neutrophil count in peripheral blood were significantly increased, and the platelet count decreased to a higher degree. Part thromboplastin time increased, D-dimer increased, but fibrinogen content decreased more. The changes of erythrocyte and hemoglobin had no significant correlation with whether Staphylococcus aureus carried virulence genes. Conclusion. The detection rate of MRSA in patients with positive Staphylococcus aureus in blood culture had exceeded 20%. The detected MRSA bacteria carried three virulence genes, tst, pvl, and sasX, which were more likely than MSSA. MRSA, which carries two virulence genes, is more likely to cause clotting disorders.